2013
DOI: 10.1016/j.matlet.2013.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal approach for the design of Ti powders sinterable at low temperature

Abstract: The colloid-chemistry control of metallic powders in aqueous slurries is proposed as a way to produce spherical granules of fine titanium particles able to be processed by powder metallurgy (PM) techniques. Significant improvement of sintering behaviour is achieved, leading to high dense parts at reduced sintering temperature and time.Consequently the control of grain growth during sintering was achieved, as well as the oxygen content. This approach can be extended to other strategies for Ti design, such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
(14 reference statements)
0
16
0
Order By: Relevance
“…Fig. 5a shows the kinetics of nano-TiN deposition for times lower than 180 s (3 min) when using stain- less steel AISI 316L (SS316L) and AISI304 (SS304) substrates and Ti substrates fabricated by pulvimetallurgy (PM) techniques [42]. Stainless steel surfaces are polished while Ti substrates have an asprepared surface.…”
Section: Epd Of Steric Stabilized Nano-tin Suspensionsmentioning
confidence: 99%
“…Fig. 5a shows the kinetics of nano-TiN deposition for times lower than 180 s (3 min) when using stain- less steel AISI 316L (SS316L) and AISI304 (SS304) substrates and Ti substrates fabricated by pulvimetallurgy (PM) techniques [42]. Stainless steel surfaces are polished while Ti substrates have an asprepared surface.…”
Section: Epd Of Steric Stabilized Nano-tin Suspensionsmentioning
confidence: 99%
“…[27] Eventually, according to Bockstiegel, [28] the interest shifted more towards an analytical problem-finding a simple but adequate mathematical description for experimentally observed compaction curves. [1,2,[6][7][8][9][10][11][12][13][14] The compaction curves for ITP-produced Ti, [12] CSIR-produced Ti, [8] Ho¨gana¨s AB produced Ti and TiH 2 , [13,17] Armstrong produced Ti and Ti-6Al-4V, [14,17] spray-dried powders, [20] for example, have also been reported Comparing the compressibility of different powder CP-Ti, sponge, HDH, and various Ti-6Al-4V powder mixtures (up to 1200 MPa) several researchers, see Refs. 1, 2, 6 through 9, 11 through 13, and 17 for example, have also studied and compared the compaction behavior of different Ti powder.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Some noteworthy findings from literature are summarized in Table I. According to Table I, many research articles have reported on the compressibility behavior of titanium powders [1,2,[6][7][8][9][10][11][12][13][14]17,20,22,25] ; evidently, only a very few have paid particular attention to the analysis of the cold compaction behavior of titanium powders using existing or new compaction equations, see References 10,12,14,22, and 25 for example. Those that have, for unspecified reasons, have selectively applied only a few models.…”
Section: Introductionmentioning
confidence: 99%
“…The spraydrying technique allows for the designing of Ti granules that are able to flow and to be processed by conventional PM techniques. Neves et al [17,18] reached a sintering density of approximately 96 % of the theoretical value through this method.…”
Section: Introductionmentioning
confidence: 84%
“…i) Polyacrylic acid (PAA, Mw=2000 g/mol, Acros Organics, USA), prepared in an tetramethylammonium hydroxide (HTMA) solution at pH 10, which was previously used in Neves et al [17,18]. …”
Section: Methodsmentioning
confidence: 99%